A study on effectiveness of female sterilization by the modified pomeroy technique in a secondary hospital - Dokchan, Nipon (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Sterilization is a highly effective method of contraception with nearly a 100% success rate. After sterilization, however, a woman may become pregnant within the first 1-2 years, or several years later. Pang Khon Hospital, Sakon Nakhon, is a secondary hospital where mothers have been found to conceive three years after sterilization by the Modified Pomeroy Technique in 1999. This research was aimed at studying the effectiveness of female sterilization by the Modified Pomeroy Technique and tying the fallopian tubes on the side adjacent to the uterus with silk along with following-up on patients one year after sterilization. Methods: This study is a retrospective study. The study was conducted in the Department of Obstetrics and Gynecology, Pang Khon Hospital, Sakon Nakhon. Data were collected retrospectively from 4,553 mothers who were sterilized in 2002-2020 (19 years). Inclusion criteria of the study participants a total 4,201 mothers were sterilized by using the Modified Pomeroy Technique and tying fallopian tubes on the side adjacent to the uterus with silk thread and exclusion criteria of the study participants were mothers who were not sterilized by using the Modified Pomeroy Technique and tying fallopian tubes on the side adjacent to the uterus with silk thread. Data was collected from patient medical records. Demographic data regarding age of patient and various parameters like parity, method of sterilization, time interval between sterilization and failure, mode of presentation were analysed with SPSS software and results tabulated. Results: No pregnancies were found among 4,201 mothers sterilized by using the Modified Pomeroy Technique and tying the fallopian tubes on the side adjacent to the uterus with silk thread. Conclusions: Female sterilization by using the Modified Pomeroy Technique and tying the fallopian tubes on the side adjacent to the uterus with silk thread is an effective method. Therefore, the aforementioned method should be a good method and option for female sterilization.